Exploring the role of Home Language (s) in the Schooling of Tribal Children of Rajasthan at the Primary Stage - Yadav , Saryug; Shukla, Abhay Kumar (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
The tribals in Indian polity are remarkable for their diverse cultures that feast on widely divergent customs and traditions. A simple dry narrative pushing a particular viewpoint of "educating children through mother tongue" may not become a critical voice for describing ground realities. Indian modernity and humanism are rumbling with cynicism, impassivity, and discontentment in a rumpus of tribal society. The issues in the present study have been interrogated afresh simultaneously guarding against creating a disparate conviction rather gaining an insightful understanding that the tribal languages could become a beacon for providing an enabling experience to tribal children for meeting both the ends of broad streaming and also preserving their identity as well as ensuring the growth of cosmopolitan functional qualities for meaningful participation in the existing global scenario.